Dithiocarbamate functionalized Al(OH)3‐polyacrylamide adsorbent for rapid and efficient removal of Cu(II) and Pb(II). Issue 46 (2nd August 2017) - Liu, Ya; Qian, Peng; Yu, Yang; Xiao, Li; Wang, Yongliang; Ye, Shufeng; Chen, Yunfa
ABSTRACT: Heavy metal ions such as Cu 2+ and Pb 2+ impose a significant risk to the environment and human health due to their high toxicity and non‐degradable characteristics. Herein, Al(OH)3 ‐polyacrylamide chemically modified with dithiocarbamates (Al‐PAM‐DTCs) was synthesized using formaldehyde, diethylenetriamine, carbon disulfide, and sodium hydroxide for rapid and efficient removal of Cu 2+ and Pb 2+ . The synthesized adsorbent was characterized by Fourier transform infrared (FTIR) spectroscopy, thermogravimetric analysis, scanning electron microscopy–energy dispersive X‐ray spectroscopy analysis, and transmission electron microscope measurements. Al‐PAM‐DTCs showed rapid removal of Cu 2+ (<30 min) and Pb 2+ (<15 min) with high adsorption capacities of 416.959 mg/g and 892.505 mg/g for Cu 2+ and Pb 2+ respectively. Al‐PAM‐DTCs also had high capacities in removing suspended solids and metal ions simultaneously in turbid bauxite suspensions. FTIR, thermodynamic study, and elemental mapping were used to determine the adsorption mechanism. The rapid, convenient, and effective adsorption of Cu 2+ and Pb 2+ indicated that Al‐PAM‐DTCs has great potential for practical applications in purification of other heavy metal ions from aquatic systems. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 45431. Abstract :